THE EFFECT OF AUDITOR EXPERIENCE, WORKLOAD AND MOTIVATION AUDITOR ON AUDIT QUALITY IN FINANCIAL AND DEVELOPMENT SUPERVISORY BOARD SOUTH OF SULAWESI - Muhammad Ishak (Salewangang Institut Publishing, 2018)
Purpose of this research is to know the simultaneous effect of auditor experience, workload and motivation auditor on the quality of the audit results on The Financial and Development Supervisory Board in South of Sulawesi. Population in this research is auditor of The Financial and Development Supervisory Board in South of Sulawesi. The results of this study indicate that: (1) Simultaneous Audit experience, Workload and Motivation Auditor has a significant impact on the quality of the audit results show the value of F 14.482 and significance of the correlation value of 0.000. (2) Audit Experience has significant influence on the quality of audit with a value of 0.002, Workload does not have a significant effect on the quality of audit with a value of 0.122 and Motivation Auditor has a significant influence on the Quality Audit with significant value of 0.011. (3) The most dominant variable influence on the value of Quality Audit Standards largest beta coefficient 0.368 or 36.8%, is Motivation Auditor.